Real or Not Real: The Hunger Games as Transmediated Religion - Ringlestein, Yonah (Journal of religion and popular culture, 2013)
Transmedia is a powerful mode of mediated storytelling. Resembling the mythic imaginaries of Jewish mysticism and Christian Gnosticism, transmedia encourages fans to perform their desire for wholeness and ultimate reality. The Hunger Games franchise does religious work of shaping desire for wholeness through fan culture by promising fans they can overcome fragmentation and experience reintegration. Cultural analyses of transmedia franchises have yet to look at the mythic pattern of fragmentation, negotiation, and reunification of self through transmedia and fan-based activities. What makes The Hunger Games distinctive is how it functions as a transmediated world and also exposes the necessity of negotiation with media to recognize the difference between artifice and reality. I conclude that The Hunger Games eschews both the singular reality of modernity and the fluid realities of postmodernity, instead advocating for a persistently critical perspective of all kinds of constructed worlds and all realities.